2011
DOI: 10.5600/mmrr.001.04.a02
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Routine Breast Cancer Screening for Medicaid Managed Care Members with a Work-Limiting Disability

Abstract: Objective: Examine disparities in routine mammography for women who qualify for Medicaid, because of a work-limiting disability. Methods: Individual-level data were obtained for women enrolled in Massachusetts Medicaid ManagedCare plans who met the 2007 Healthcare Effectiveness Data and Information Set (HEDIS) criteria for the breast cancer screening measure (n=35,171). Disability status was determined from Medicaid eligibility records. Mammography screening was modeled using multivariate logistic regression. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…14,15 Within the research literature, a large number of predictors of decreased participation have been identified; for example, increased disability severity has been found to be a predictor of decreased participation for all types of cancer screening. 4,5,9,10,14,[16][17][18][19][20][21][22] For people with breast cancer, other disability related predictors of decreased participation include having major lower limb difficulties, 23 being non-ambulatory, 24 using mobility aids, 25 living farther from facilities that offer mammography 26 or having a relative as the main caregiver as opposed to a spouse/partner caregiver. 27 For women with cervical cancer, other disability related predictors of non-participation include having multiple disabilities, 16 having lower limb difficulties, 23 having a relative caregiver as opposed to a spouse/partner caregiver 27 and requiring caregiving for activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…14,15 Within the research literature, a large number of predictors of decreased participation have been identified; for example, increased disability severity has been found to be a predictor of decreased participation for all types of cancer screening. 4,5,9,10,14,[16][17][18][19][20][21][22] For people with breast cancer, other disability related predictors of decreased participation include having major lower limb difficulties, 23 being non-ambulatory, 24 using mobility aids, 25 living farther from facilities that offer mammography 26 or having a relative as the main caregiver as opposed to a spouse/partner caregiver. 27 For women with cervical cancer, other disability related predictors of non-participation include having multiple disabilities, 16 having lower limb difficulties, 23 having a relative caregiver as opposed to a spouse/partner caregiver 27 and requiring caregiving for activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
“…The following supporting information can be downloaded at: , Supplementary Table S1: Detailed reasoning for exclusion of articles after full-text screening; Supplementary Table S2: Characteristics of the included studies in the systematic review [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 ]; Supplementary Table S3: Quality assessment of included studies; Supplementary Table S4: Barriers to BC screening estimated in the included 53 studies.…”
mentioning
confidence: 99%